Perbedaan Efektivitas Terapi Musik Klasik Dan Aromaterapi Peppermint Terhadap Perubahan Skala Nyeri Pada Ibu Post Sectio Caesarea - Aprilian, Esa; Elsanti, Devita (Jurnal Keperawatan Muhammadiyah, 2020)
Background : World Health Organization (WHO) has issued a standard regulation that the average number of sectio caesarean (SC) operation in a country is 10-15% per 100,000 births. However, in 2015 it was estimated that 22.5% of labors around the world were conducted through SC. SC can cause trauma in the incision area and cause pain. Non-pharmacological techniques that can be implemented to reduce the pain include therapy using classical music and peppermint aromatherapy. Objective : Identifying the differences in the effectiveness of therapy between using classical music and peppermint aromatherapy on the change of pain scale in post section caesarean mothers. Metode : The research samples consisted of 44 post sectio caesarea mothers in RSIA Bunda Arif Purwokerto. The samples were divided into two groups and were selected through consecutive sampling. The research instrument was an observation sheet with Mann Whitney test. Result : Most of the respondents are 21-35 years old on the group of classical music therapy (72.7%) and peppermint aromatherapy (86.4%), have senior high school education degree (45.5%), multipara parity of classical music therapy (68.2%) and of peppermint aromatherapy (72.7%), never get SC history before (68.2%), housewives in classical music therapy (50%) and in peppermint aromatherapy (54.5%). The result of p-value bivariate test is 0.038, indicating that there is a significant difference between therapy using classical music and peppermint aromatherapy. The average difference between classical music therapy is 2.97, and peppermint aromatherapy is 3.34. Conclusion : Peppermint aromatherapy is more effective to reduce pain scale in post sectio caesarea than classical music theraphy. Keywords : Sectio caesarea, pain, classical music therapy, peppermint aromatherapy